Conduction systems in fig tree with two cultivars, evaluating fruits quality and yield - Ecker, Scheila Lúcia; Lugaresi, Adriana; Girardi, Gian Carlos; Louis, Bachelor; Galon, Leandro; Giacobbo, Clevison Luiz (Scientia Agraria Paranaensis, 2020)
The fig tree is rustic and one of the fruit species with great economic importance, because it adapts easily to different climate and soil types. The objective of this study was to evaluate the influence the branches number and the fig tree cultivar on yield and fruit quality. The orchard implanted with two cultivars, Roxo de Valinhos and Pingo de Mel, and conducted with different numbers of productive branches, being: 16, 24 and 32. The utilized lineation was completely randomized, with three replicates, each replicate being composed of four plants. The analyzed variables were: branches length (cm), number of fruits per plant, number of fruits per branch meter, yield of mature fruits (Kg ha-1), yield of green fruits (Kg ha-1), accumulated productivity (Kg ha-1), fruit size (cm3), average fruit weight (g), soluble solids (°Brix) and fruit dry matter (%). The daily elongation rate and the mean length of the branches did not influence the different treatments. For productivity, noticed superiority on cultivar Roxo de Valinhos, with the higher the number of productive branches in the plants. Fruit quality, relative to soluble solids and dry matter, also did not influence the treatments. Fruits in larger caliber and size found from plants of the cultivar Roxo de Valinhos. Both for the production of fruits for fresh consumption and for the industrialization it is recommended the conduction with greater number of productive branches being between 24 and 32, for the greater productive yield.